DETERMINAN KOMPONEN INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN KEPULAUAN MADURA 2010-2017 - Dian Anggita; Wahyu Hidayat Riyanto (Jurnal Ilmu Ekonomi, 2021)
The human development index is one of the measuring tools used to assess the quality of human development in an area by looking at the effects of physical conditions in the form of welfare and health and non-physical, namely education. The purpose of this study is to analyze mean years school (MYS) and per capita expenditure on the human development index in Madura Islands district from 2010 to 2017. The data used in this study is a secondary data obtained from Badan Pusat Statistik using the methods of data collection that is used is the study of documenting. The analytical tool used in this study is the panel data multiple regression method with the Fixed Effect Model (FEM).  The results showed that the variable mean years school (MYS) and per capita expenditure  had a positive and significant effect on the human development index in Madura Islands district. Variable mean years school (MYS) has a greater effect on the human development index in the madura islands district than the variable per capita expenditure.The human development index is one of the measuring tools used to assess the quality of human development in an area by looking at the effects of physical conditions in the form of welfare and health and non-physical, namely education. The purpose of this study is to analyze mean years school (MYS) and per capita expenditure on the human development index in Madura Islands district from 2010 to 2017. The data used in this study is a secondary data obtained from Badan Pusat Statistik using the methods of data collection that is used is the study of documenting. The analytical tool used in this study is the panel data multiple regression method with the Fixed Effect Model (FEM).  The results showed that the variable mean years school (MYS) and per capita expenditure  had a positive and significant effect on the human development index in Madura Islands district. Variable mean years school (MYS) has a greater effect on the human development index in the madura islands district than the variable per capita expenditure.